The Slaves’ Foods: A Gastronomy Analysis in Uncle Tom’s Cabin by Harriet Beecher Stowe - Andy Amiruddin; Khairil Anwar; Ferdinal Ferdinal (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2020)
This paper discusses the foods eaten by the slaves from Uncle Tom’s Cabin about the nature of slavery that happens in South America. There are two contrast setting of places in the novel—Kentucky and Louisiana—that each has different food presentations for the slaves, and each presentation can reveal the power relation between masters and slaves. In gastronomy, when food is done right in writing, certain scenes from fiction can get the readers to experience it with all their senses and strange cravings. The finding in this writing is that the slaves creatively change the scraps and leftovers into finely soul foods of in the first set of the place, Kentucky. The second setting is a place in Louisiana, the slaves cannot have the soul food because the lack of food itself has chained them forever in the slavery. Each of this food presentations has directly revealed the nature of power relation between masters and slaves.